For learning a new language of 6th and 7th grade children, at Jorge Escudero Moscoso Public school during the school year September 2006 June 2007 - Villavicencio Almeida, María Augusta (2008)
The following is a dissertation, which deals with the situation of the Children s migrants, after the economic and political crisis in 1999 which caused the familiar division and the abandon of many children in some cases. This research looks for establishing the motivation to study the English language in a poor Public School of Quito. The first part of the present work begins with the identification of the problem, the problem setting, the general and specific objectives and the justification in order to accomplish this research. The second part reviews the academic literature related with the general topic; this part contains the structure of the research, in the first chapter and deals with: social consequences from migration and the recent wave of migration abroad, Historical background, migrant s destination, migrant s status, family disorganization and low performance; economical impacts; and political issues. The second chapter focuses on motivation degree in Children through the support and care that relatives and tutors give them. It also mentions children maltreatment, prevention policies and children rights. In this part, it is interesting to know the point of view of teachers and the responsibility of educating...